2007
DOI: 10.1111/j.1464-5491.2007.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐normal levels of albuminuria predict the development of micro‐ and macroalbuminuria and increased mortality in Brazilian Type 2 diabetic patients: an 8‐year follow‐up study

Abstract: In normoalbuminuric Type 2 DM patients, the development of micro- or macroalbuminuria and mortality rates was independently and positively associated with higher levels of albuminuria, although still in the traditionally established normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
4
31
0
1
Order By: Relevance
“…This idea is corroborated by our own previous findings, as well as by those of other studies, which have demonstrated that even "highnormal" albuminuria may be predictive of advanced kidney disease and mortality 1,21 . Surprisingly, it was only recently that a candidate liquid chromatography-mass spectrometry (LC-MS/ MS) was developed as a reference measurement procedure to assess UA 22 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This idea is corroborated by our own previous findings, as well as by those of other studies, which have demonstrated that even "highnormal" albuminuria may be predictive of advanced kidney disease and mortality 1,21 . Surprisingly, it was only recently that a candidate liquid chromatography-mass spectrometry (LC-MS/ MS) was developed as a reference measurement procedure to assess UA 22 .…”
Section: Discussionsupporting
confidence: 80%
“…Diabetic kidney disease (DKD) is a serious microvascular complication of diabetes mellitus (DM), and the leading worldwide cause of end-stage renal disease 1,2 . The early detection of DKD allows for the use of strategies to halt its development or at least delay the progression of the disease 3 .…”
mentioning
confidence: 99%
“…The univariate analysis indicated that, in comparison to that of a normoalbuminuria group, the microalbuminuria development group had longer diabetes duration (9.34 vs. 7.95 years), had more subjects on insulin therapy (32.4% vs. 14.2%), had a poorer glycemic control (8.71% vs. 7.78%), and had a higher baseline UACR (15.31 mg/g vs. 9.85 mg/g) ( Table 1). Though more hypertension subjects were included (44.1% vs. 34.4%) in the microalbuminuria development group (p ¼ 0.052), the average blood pressure levels were similar between the microalbuminuria and control groups.…”
Section: Resultsmentioning
confidence: 97%
“…1,2 Approximately 40% of all diabetic patients develop DN, 3 which is the most common diagnosis among individuals in renal replacement programs, accounting for up to 44% of cases. 4 In Brazil, in 2010, 27.5% of patients on dialysis had DN, and it is likely that in the coming years a significant increase in the number of diabetic patients undergoing dialysis therapy occurs.…”
Section: Introductionmentioning
confidence: 99%